The development of motor creativity in elementary school children and its retention - Bournelli, P.; Mountakis, K. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction A follow-up study was contacted in order to find whether motor creativity, which was developed in elementary school children of the third grade nine years ago with the implementation of a Special Physical Education Program, could be retained. It was found that the experimental group continues to show statistically significant superiority in motor creativity. Methods The Special Physical Education Program was implemented in elementary school children of the third grade (9 years old). The evaluation of motor creativity of the pupils was measured with the motor creativity test of Wyrick, (1966) [1]. The original experiment lasted one school year. All information concerning details of the methodology, measurements, implementations and analysis of the original experiment are included in earlier publications [2]. Nine years later a follow-up study with measurements was contacted using the same children when they were at their final year in the Lyceum (18 years old). The data of motor creativity were assessed in three stages: a) The first stage, was conducted before commencing the experiment Both groups (experimental and control) were asked to perform three different tasks (the parallel lines test, ball wall test, and hoop test). b) For the second stage, after the completion of the Special Physical Education Program for the experimental and the control group, the same measures were used (one year after baseline assessment). c) For the follow-up stage, nine years later, under no other special program for the experimental group, the same three measures were used in both groups, as well. All the testing process was video taped and analyzed latter in order to avoid mistakes. Results The data were analyzed through simple analysis of variance designs with repeated measures. The between subjects factor was the two groups (experimental and control) and the repeated measures factor (within subjects) comprised of the three trials for each task. All the results are presented in a graph.